Optimizing Care for Ugandans with Untreated Abdominal Surgical Conditions - Elissa K. Butler; Tu M. Tran; Anthony T. Fuller; Christine Muhumuza; Sarah Williams; Joao R. N. Vissoci; Samuel Luboga; Michael M. Haglund; Fredrick Makumbi; Moses Galukande; Jeffrey G. Chipman (Ubiquity Press, 2019)
Background: Abdominal operations account for a majority of surgical volume in low-income countries, yet population-level prevalence data on surgically treatable abdominal conditions are scarce. Objective: In this study, our objective was to quantify the burden of surgically treatable abdominal conditions in Uganda. Methods: In 2014, we administered a two-stage cluster-randomized Surgeons OverSeas Assessment of Surgical Need survey to 4,248 individuals in 105 randomly selected clusters (representing the national population of Uganda). Findings: Of the 4,248 respondents, 185 reported at least one surgically treatable abdominal condition in their lifetime, giving an estimated lifetime prevalence of 3.7% (95% CI: 3.0 to 4.6%). Of those 185 respondents, 76 reported an untreated condition, giving an untreated prevalence of 1.7% (95% CI: 1.3 to 2.3%). Obstructed labor (52.9%) accounted for most of the 238 abdominal conditions reported and was untreated in only 5.6% of reported conditions. In contrast, 73.3% of reported abdominal masses were untreated. Conclusions: Individuals in Uganda with nonobstetric abdominal surgical conditions are disproportionately undertreated. Major health system investments in obstetric surgical capacity have been beneficial, but our data suggest that further investments should aim at matching overall surgical care capacity with surgical need, rather than focusing on a single operation for obstructed labor.